Development of Escape Room Game-Based Interactive Learning Media to Improve Grade 3 Students' Understanding of Environmental Materials - Rahmawati, Nensy Amalia Nur; Aka, Kukuh Andri; Mukmin, Bagus Amirul (Advances In Social Humanities Research, 2025)
This study aims to develop and test the effectiveness of escape room-based interactive learning media in improving the understanding of 3rd grade elementary school students to environmental materials. The background of this development is that there is still a low interest in learning and students' understanding of environmental materials due to conventional learning methods that are less attractive. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Validation was carried out by material experts and media experts with results showing feasibility rates of 91.6% and 90%. The practicality test showed that this medium was very practical with a score of 97% of teachers and 94% of students. The results of the effectiveness test also showed that this medium was very effective with a completeness rate of 93.33% in the limited test and 93.21% in the broad test. This learning medium not only increases students' motivation to learn, but also encourages active participation, critical thinking, and cooperation in groups. Thus, the use of escape room media in learning makes a significant contribution to improving the quality of learning environmental materials in elementary schools.